Implementasi Rangkaian LED dan DC Water Pump pada Miniatur Taman sebagai Media Belejar untuk Siswa Difabel - Sirojul Hadi; Anthony Anggrawan; M Najmul Fadli; Kurniadin Abd Latif; Muhammad Zulfikri; Tomi Trisujaka; Rini Anggriani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Students with disabilities are special students who have equal opportunities to be independent and able to develop themselves. Through learning and increasing creativity and innovation, students with disabilities will be able to compete and contribute to progress and development of self-ability in the community environment. The rapid development of technology requires children to learn from an early age. The first step to foster children's interest in learning about technology is to create technology-based learning media. Therefore community service is carried out with the aim that students with disabilities can learn about technology and can create a work that is used as a medium for learning about technology. The PkM method used is the experimental method. The result of the PkM that has been implemented is that students can enthusiastically learn about technology such as making led circuits and water pump circuits. Six deaf students were able to successfully make LED circuits and water pump circuits for a miniature garden.